RISK MANAGEMENT ANALYSIS OF BUS TRANSPORTATION APPLICATION USING COBIT 4.1 - Resad Setyadi; Handy Nur Prabowo (STMIK Royal, 2021)
Abstract: The role of information technology in transportation increases, namely in enjoying transportation services. One way to provide the best service for a transportation company to customers is to provide a bus booking application service. One of the companies that offer service applications is a bus transportation application located in Yogyakarta. Because the application system is considered necessary, stakeholders need IT risk management for the bus booking application. The purpose of this research is to analyze the risk management of the bus transportation application. In measuring IT risk management, the author uses the Control Objective for information and Related Technology (COBIT) 4.1 domain Plan and Organize (PO) framework, especially PO9 (Assess and Manage IT risk). The analysis results show that if the bus transportation application is at level 2 in maturity level. It means that the company knows that there are problems that need resolving. Standard risk management in bus transportation applications tends to provide failed access in the progress of its service. The problem is solving individually and not yet at the integrated completion stage. In general, the application management approach needs to improve better management in the field of information technology. Keywords: COBIT; plan and organize; risk management Abstrak: Peran teknologi informasi dalam meningkatnya angkutan yaitu dalam menikmati layanan angkutan. Salah satu cara untuk memberikan layanan terbaik bagi perusahaan angkutan kepada pelanggan adalah dengan menyediakan layanan aplikasi pemesanan bus. Salah satu perusahaan yang menawarkan aplikasi jasa adalah aplikasi angkutan bus yang berlokasi di Yogyakarta. Karena sistem aplikasi dirasa perlu, maka stakeholders membutuhkan manajemen risiko TI untuk aplikasi pemesanan bus tersebut. Tujuan dari penelitian ini adalah menganalisis manajemen risiko pada aplikasi angkutan bus. Dalam mengukur manajemen risiko TI, penulis menggunakan framework Control Objective for Information and Related Technology (COBIT) 4.1 domain Plan and Organize (PO), khususnya PO9 (Assessment and Manage IT risk). Hasil analisis menunjukkan bahwa penerapan angkutan bus berada pada level 2 pada tingkat kematangan. Artinya perusahaan mengetahui bahwa ada masalah yang perlu diselesaikan. Manajemen resiko standar dalam aplikasi transportasi bus cenderung memberikan akses yang gagal dalam kemajuan layanannya. Masalahnya diselesaikan secara individu dan belum pada tahap penyelesaian terintegrasi. Secara umum, pendekatan manajemen aplikasi perlu meningkatkan manajemen yang lebih baik di bidang teknologi informasi. Kata kunci: COBIT; plan and organize; risk management